Foundations of style in the Elizabethan sermon - Opie, Brian John (The University of Edinburgh, 1973)
The analysis and discussion of Elizabethan sermon styles and major psychological and conceptual problems which participate in the formation of these styles is approached in two ways, of which the first investigates the sermons themselves, and the second, specific controversial and discursive works. Since the primary evidence of style is the distinctive existence of any given sermon, the sermons are analysed for the information which they provide on three deeply implicated fields: the context of the sermon, with special attention given to the preacher's perception of and theories about his own function,about his relation to his audience, and about the individual and corporate natures of that audience; the text of the sermon, that is, the manner in which the Biblical text is interpreted and influences the organisation of the sermon; and the modes of argumentation by which the multiple possibilities of the text are made to realise particular purposes. In order to indicate more exactly the nature of changes taking place in the Elizabethan sermon, the period has been broadly divided into two parts, with Archbishop Grindal's letter to the Queen on 20 December 1576, defending the puritan exercises,as the symbolic point of division. For efficient comparison it has been necessary to make reference to preachers of the generation before 1558, and to provide a specific control upon interpretation three sermons from each portion of the Elizabethan period have been chosen and are the subject of comparative analysis. The purpose of this analysis is to discover what may be called semantic forms in the three sermons, understanding these to be verbal structures synthesising dominant experiential and cognitive concerns which have been progressively elaborated in the preceding discussion. Sermon style is identified with these expressive forms, and not only with rhetorical categories or literary-aesthetic determinations. The second part provides another perspective upon particular questions which arise in the sermons, and upon the broad underlying movements in the experience and conception of which style is the most sensitive register. Once again this part is divided into two sections: in the first, certain aspects of two major controversies of special relevance in the formation of the Elizabethan church, those between Jewel and Harding, and Whitgift and Cartwright, are shown to localise issues of much more general significance; and in the second, three subjects which further reveal conceptual problems fundamental to the evolution of Elizabethan thought,in the areas of psychology, logic and rhetoric, and science are investigated. While these subjects involve all thinking men of the period in some way,/interactive relation with the sermon analysis is maintained by concentrating principally upon clerical representation of them. It becomes apparent that consideration of style in terms of literary values or terminology is inadequate both to characterise those elements of prose expression which represent the distinctive features of the thought and experience of individuals or groups, and to correlate the descriptions of these expressive forms with areas of development in the culture of a particular period where contemporaneous definition of concepts,apart from these forms, is necessarily lacking. The classifications attempted are understood to be indicative rather than definitive, since the relation between the content of a culture, the quality of its realisation in individual and group consciousness, and its communication and transformation, is of extreme complexity. It is more clearly focussed in the consideration of what was known or believed, and what was perceived as uncertain or unknowable, about human nature itself and the external world, and particularly about the nature and function of language as the means of relation.